Study on microstructure characterization of fracture frontier of post welds heat treatment and type IV cracking of P92 steel welded joinT - Pal, Vinay Kumar; Singh, Lokendra Pal (Видавництво Львівської політехніки, 2022)
In the research work presented in this study microstructure evolution at fracture frontier of crept P92 weld, creep rupture life and effect of creep exposure time on microstructure evolution in fine-grained heat affected zone were performed. Microstructure evolution and creep rupture behavior of metal arc welded joint of P92 steel plate in the as-welded have been studied. The different states of post weld heat treatment (PWHT). (i). post welded heat treatment at 760 °C for the 2h (ii). re-austenitizing at 1040 °C for 60 min and air cooled and tempering at 760 °C for 2h. In PWHT condition, most common type IV cracking was observed creep exposure 620 °C / 150 MPa. The martensitic matrix fracture is also observed in PWNT 1 condition. A move away from the fracture frontier, the cavities still remain in the microstructure while the martensitic matrix fracture is difficult to observe. The line mapping also confirmed the increase in weight percentage of Cr and Mo in M23C6. The elemental mapping of PWHT 2 condition is also carried out in FGHAZ which confirm the formation of Mo and Cr-rich M23C6 precipitates.
Keywords: leaves phase; PWHT; fracture frontier; P92 Steel; element mapping; creep rupture; microstructure